El imperfecto y el indefinido español. Una investigación para la enseñanza de los tiempos pasados en Islandia - González, Juan Aguilar, 1979- (2015)
Learning a language is an activity that provides great satisfaction, although the difficulty of some grammar topics can be discouraging. In the case of Icelandic students of Spanish, learning the past tenses stands out as one of those problems that can be solved only after many years and a lot of effort devoted to it. This paper is intended to help students (and teachers) to learn and teach in an efficient way the imperfect and past simple, as well as the contrast between them. To do so, a brief review of how they are taught nowadays in the ELE classroom has been carried out. Nevertheless the core of this work relies on the teaching unit and its activities, which have been designed with a practical purpose, without recourse to the theoretical thoughts that often accompany grammars, which does not help much the foreign student. Finally, with the idea of establishing solid knowledge, special care has been taken in order not to fix ideas that may lead to error when deepening in the study of Spanish.